Asymptomatic fatal post-lobectomy hemopericardium - C. Kotoulas; S. Meraj; N.J. Odom (Monaldi Archives for Chest Disease, 2016)
We report a case of an asymptomatic post-lobectomy hemopericardium in a female who died suddenly at day two post surgery. Autopsy revealed no pathologic findings, but 250 ml of blood and clots in the pericardium and a non-significant injury to the epicardial fat overlying the circumflex artery territory.